Efficacy and safety of percutaneous transforaminal endoscopic surgery (PTES) compared with MIS-TLIF for surgical treatment of lumbar degenerative disease in elderly patients: A retrospective cohort study - Ma, Tianle; Zhou, Tianyao; Gu, Yutong; Zhang, Liang; Che, Wu; Wang, Yichao (Frontiers in Surgery, 2023)
Objectives: To evaluate the efficacy and safety of PTES for surgical treatment of lumbar degenerative disease (LDD) including lumbar disc herniation, lateral recess stenosis, intervertebral foraminal stenosis and central spinal canal stenosis in elderly patients compared with MIS-TLIF. Methods: From November 2016 to December 2018, 84 elderly patients (>70 years old) of single-level LDD with neurologic symptoms underwent the surgical treatment. 45 patients were treated using PTES under local anesthesia in group 1 and 39 patients treated using MIS-TLIF in group 2. Preoperative, postoperative back and leg pain were evaluated using Visual analog scale (VAS) and the results were determined with Oswestry disability index (ODI) at 2-year follow-up. All complications were recorded. Results: PTES group shows significantly less operation time (55.6±9.7min vs 97.2±14.3min, P<0.001), less blood loss [11(2-32)ml vs 70(35-300)ml, P<0.001], shorter incision length (8.4±1.4mm vs 40.6±2.7mm, P<0.001), less fluoroscopy frequency [5(5-10) times vs 7(6-11) times, P<0.001] and shorter hospital stay[3(2-4) days vs 7(5-18) days, P<0.001] than MIS-TLIF group does. Although there was no statistical difference of leg VAS scores between two groups, back VAS scores in PTES group were significantly lower than those in MIS-TLIF group during follow-ups after surgery (P<0.001). ODI of PTES group was also significantly lower than that of MIS-TLIF group at 2-year follow-up (12.3±3.6% vs 15.7±4.8%, P<0.001). Conclusion: Both PTES and MIS-TLIF show favorable clinical outcomes for LDD in elderly patients. Compared with MIS-TLIF, PTES has the advantages including less damage of paraspinal muscle and bone, less blood loss, faster recovery, lower complication rate, which can be performed under local anesthesia.